ANALISIS PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Berlian Dea Permatasari; Lilik Farida; Susanti Prasetiyaningtiyas; Intan Nurul Awwaliyah; Ahmad Ahsin Kusuma (VALUE: Journal of Business Studies, 2023)
This study aims to analyze the effect of financial ratios on firm value in infrastructure, utility, and transportation sector companies listed on the Indonesia Stock Exchange. The research data is secondary data (pooling data) obtained from the financial statements of companies in the infrastructure, utilities, and transportation sectors listed on the Indonesia Stock Exchange during the 2016-2020 period. The research method used is Multiple Linear Regression Analysis. The population in this study consisted of infrastructure, utility, and transportation companies listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling technique and obtained as many as 40 companies according to the criteria. The test results show that the activity ratio (TATO) at alpha 5% has a significant effect on firm value (PBV) and the leverage ratio (DAR) at alpha 1% has a significant effect on firm value (PBV). While the liquidity ratio (Cash Ratio) and profitability ratio (ROE) have no significant effect on firm value (PBV).